Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/w13010109
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Hydraulics in a Drinking Water Distribution System Influence Suspended Particles and Turbidity, But Not Microbiology

Abstract: Spatial and short-term temporal changes in water quality as a result of water age and fluctuating hydraulic conditions were investigated in a drinking water distribution system. Online measurements of total and intracellular adenosine tri-phosphate (ATP), total and intact cell concentrations measured with flow cytometry (FCM), turbidity, and particle counts were performed over five weeks at five subsequent locations of the distribution system. The high number of parallel FCM and ATP measurements revealed the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
2
17
1
Order By: Relevance
“…Studies have shown that, when compared to WDSs with high velocity water flows (>0.3 m/sec), those with low velocity flows have lower hydrodynamic shear forces at the internal surface of their pipes, which leads to growth of thicker, less dense and less stable biofilms [ 41 , 42 , 43 ]. Further to this, low velocity water flows through pipes lead to higher concentrations of antimicrobial-resistant bacteria (ARB) and a higher prevalence of antimicrobial-resistant genes (ARGs), and different microbial community compositions than are found in pipes with higher velocity water flow [ 44 , 45 , 46 ]. Exposure of microbial communities in biofilms to sub-inhibitory antimicrobial concentrations, which is likely in pig building WDSs, especially during lower metaphylactic in-water dosing events conducted over >12 h, could also modulate biofilm matrix composition.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that, when compared to WDSs with high velocity water flows (>0.3 m/sec), those with low velocity flows have lower hydrodynamic shear forces at the internal surface of their pipes, which leads to growth of thicker, less dense and less stable biofilms [ 41 , 42 , 43 ]. Further to this, low velocity water flows through pipes lead to higher concentrations of antimicrobial-resistant bacteria (ARB) and a higher prevalence of antimicrobial-resistant genes (ARGs), and different microbial community compositions than are found in pipes with higher velocity water flow [ 44 , 45 , 46 ]. Exposure of microbial communities in biofilms to sub-inhibitory antimicrobial concentrations, which is likely in pig building WDSs, especially during lower metaphylactic in-water dosing events conducted over >12 h, could also modulate biofilm matrix composition.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Fish et al (2020) found that TCC and ICC mobilised into the bulk water from biofilms was inversely correlated with turbidity and metals (iron and manganese) concentrations during flushing trials within an experimental DWDS. Similarly, Prest et al (2021) found hydraulics impacted particle counts and turbidity, but not TCC and ICC in the bulk water within operational DWDS. Although the EPS and community composition within the biofilm is likely to influence the biofouling rate, current analysis approaches are time consuming, costly and require substantial biomass for accurate data.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, Ikonen et al. (2013) , McCoy and Olson (1986) , Prest et al. (2021) showed only a weak correlation between microbial water quality and turbidity for a drinking water distribution system and a municipal drinking water treatment plant.…”
Section: Introductionmentioning
confidence: 82%